Predicting the Recovery of Pinus halepensis and Quercus ilex Forests after a Large Wildfire in Northeastern Spain (Plant Ecology, 2005)
Quercus ilex and Pinus halepensis are two of the most common tree species of the western Mediterranean basin. Both species regenerate reliably after ﬁre: P. halepensis colonizes recently disturbed areas by eﬀective seedling recruitment, while Q. ilex resprouts vigorously after disturbances. For this reason, the natural regeneration of these species after ﬁre should ensure the re-establishment of a forest similar to that which existed before the ﬁre. This study analyzes with a simple simulation model whether or not the relative abundance of monospeciﬁc and mixed forests of these species in the landscape is altered by ﬁre. We also analyze the topographic factors and the forest structure before the ﬁre that determine the changes in forest composition after ﬁre. This study has been carried out in a large ﬁre that occurred in NE Spain. Overall, 33% of plots changed to another community type, but this probability of change varied considerably among community types before the ﬁre. Monospeciﬁc forests of P. halepensis or Q. ilex had a high probability of remaining in their original composition after the ﬁre, whereas the resilience of mixed forests of these two species was quite low. Mixed forests changed for the most part to monospeciﬁc P. halepensis or Q. ilex forests. Analysis of several factors determining these changes indicated that only elevation as a signiﬁcant topographical variable. The eﬀect of ﬁre was to increase the altitudinal diﬀerentiation between the two species. P. halepensis forests that changed to mixed or Q. ilex forests were those of highest elevation, while the mixed and Q. ilex plots that changed to P. halepensis forests were those located at the lowest elevations. Concerning structural variables before ﬁre, density of Q. ilex trees before the ﬁre showed a much greater eﬀect than P. halepensis density in determining the post-ﬁre community. Finally, burn severity also inﬂuenced the changes observed. For both P. halepensis and Q. ilex forests, plots that changed to another forest type were mainly those that burned more severely. In the case of mixed forests, even low ﬁre severities involved high probabilities of change to monospeciﬁc forests.